Phytochemical Screening and Total Phenolic Compounds of Red Ginger (Zingiber officinale) and Secang Wood (Caesalpinia sappan) As Preliminary Test of Antiarthritis - Rizka Tazky Amalia; Tukiran Tukiran; Fauzia Indah Sabila; Suyatno Suyatno (Departemen Kimia, 2021)
Rheumatoid arthritis is an auto-immune disease that causes chronic inflammation occurs of the joints. Rheumatoid arthritis is characterized by the the overproduction of proinflammation cytokines such as TNF-α and IL-1. The phenolic compounds mainly anthocyanin and elagitanin have TNF-α inhibition activity that induces cyclooxygenase-2 expressions that cause inflammation. Phytochemical screening showed that ethanol extract of red ginger contains alkaloids, phenolics, flavonoids, tannins, terpenoid, and steroids while ethanol extract of secang wood contains alkaloids, phenolics, flavonoids, tannins, and terpenoid. This research aims to identify the secondary metabolite qualitatively and total phenolic compunds on red ginger and secang wood with Folin-Ciocalteu method. Total phenolic compounds are defined as the Gallic Acid Equivalent (GAE). The results showed that the total phenolic compunds of red ginger and sappan wood were 21.90 mg GAE/g extract and 27.65 mg GAE/g extract, respectively. The phenolic compounds in red ginger and secang wood have the potential as antiarthritic.